MiR-20a promotes osteogenic differentiation in bone marrow-derived mesenchymal stem/stromal cells and bone repair of the maxillary sinus defect model in rabbits - Wang, Yi-Xuan; Peng, Zhu-Li; Sun, Zhi-Wen; Pan, Yan-Jun; Ai, Hong; Mai, Zhi-Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: This study aimed to determine whether miR-20 promoted osteogenic differentiation in bone marrow-derived mesenchymal stem/stromal cells (BMSCs) and accelerated bone formation maxillary sinus bone defect model in rabbit. Methods: BMSCs were transfected with miR-20a or anti-20a for 24 hours, followed by detection of RUNX2, Sp7 mRNA, bone morphogenetic protein 2 (BMP2) and RUNX2 protein expression. Alkaline phosphatase (ALP) activity and Alizarin Red S staining was used to detect calcified nodule deposition. In the rabbit maxillary sinus bone defect model, miR-20a loaded with AAV and BMP2 protein were mixed with Bioss bone powder for filling the bone defect. At 4 weeks and 8 weeks, bone density was detected by cone beam computed tomography (CBCT), and new bone, osteoblasts, and collagen type 1 were evaluated by hematoxylin and eosin (HE) staining and immunohistochemical (IHC) staining. Results: Overexpression of miR-20a enhanced the mRNA and protein levels of BMP2, RUNX2, and SP7, the activity of ALP, and the levels of matrix mineralization; whereas, the levels and activity of above factors were decreased by anti-miR-20a treatment of BMSCs. Furthermore, miR-20a significantly increased the bone density, the number of osteoblasts, and the secretion of collagen type 1 in bone defects compared with Bioss bone powder in the rabbit maxillary sinus bone defect model. Conclusion: Overall, miR-20a can induce osteogenic differentiation in BMSCs and accelerate bone formation of maxillary sinus defects in rabbits.